Impact of Succession Planning on Talent Retention at Orange – Jordan - Al-Mohaisen, Faisal; Al-Kasasbeh, Mohammed (Jordan Journal of Business Administration, 2021)
This study aimed at recognizing the impact of succession planning on talent retention at Orange – Jordan. To achieve the purpose of the study, the descriptive analytical approach was used. A questionnaire was developed and distributed to the study sample which consisted of 317 employees at Orange – Jordan. The study reached a number of findings, most importantly: there is an impact of succession planning on talent retention and there is an impact of succession planning on compensation, job characteristics, career advancement opportunities and supervisors’ support at Orange -JordanThe researchers recommended that Orange– Jordan should continue to link succession planning with the company's strategy and constantly implement the succession plan because of its impact on the talent retention process and each of its dimensions: compensation, job characteristics, career advancement opportunities and supervisors’ support. This could be done through development of talent retention and succession policy, which provides guidelines for managers during implementation. Orange– Jordan should adopt a systematic methodology in the long-term succession planning.